Methodical Aspects of Disposal of Dead Animals in the Elimination of the Epizootic Focus - D. L. Poklonskii; A. V. Matveev; D. E. Chifanov; O. Yu. Durilov; D. A. Zigin; N. V. Ermilov; E. E. Lagutkina; G. G. Eremin (Вестник войск РХБ защиты)
The members of the executive bodies of the Yamalo-Nenets Autonomous Okrug (District) (YaNAO) organized the interaction on assistance in emergency response between the Ministry of Defence of the Russian Federation and the Troops of Radiological, Chemical and Biological Protection of the Russian Federation Armed Forces (hereinafter referred to as the troops of RCBP) during the elimination of the epizootic anthrax in this constituent territory of the Russian Federation. The practical implementation of this mission by the troops of RCBP was complicated by the mass mortality of animals on a vast territory, the lack of access roads, the difficulty of delivering specialized equipment, and the impossibility of transporting dead animals, taking into account the requirements of the regulations «Veterinary and Sanitary Rules for Collection, Utilization and Destruction of Biological Waste». Experts of the FSBI «48 Central Research Institute» of the Russian Ministry of Defence proposed a technical solution for the utilization of animal dead bodies by means of incineration using oil products and rubber technical goods with subsequent disinfection as part of the provision of scientific and methodological support for the localization and elimination of the epizootic in the Yamal-Nenets Autonomous Okrug. The implementation of this technical solution involves the following measures: a pallet is constructed on the surface in the immediate vicinity of the dead animal, consisting of used tires. Then, in the interior space of the pallet, a «cutting» of used truck tires (hereinafter referred to as «TT») is laid; the animal's corpse is stacked on a pallet, overlaying it on the windward side and on top of the TT; pour oil on pallet and on the corpse of animal and TT; produce arson of petroleum products in compliance with safety requirements. In this way, more than 1.5 thousand corpses of dead deer and 10 dogs were promptly disposed in the territory of 100x110 km. Simultaneously, the need to clarify (supplement) the existing regulatory and methodological framework for ensuring effective disinfection measures and utilization of corpses of dead animals was identified.